Oman : les chrétiens peuvent librement pratiquer - Janva, Michel (Le Salon Beige, 2016)
Marc Fromager montre que dans le sultanat d'Oman, les chrétiens vivent libres : "[…] Oman est un très vieil État remontant aux premiers siècles de notre ère. La monarchie est absolue, […]
Keywords: Christianisme -- Oman

الحملات التنصيرية الى عمان والعلاقة المعاصرة بين النصرانية والاسلام: درسة - الحسيني, سليمان بن سالم (جامعة نزوى, 2014)
Evangelical missions to Oman and the contemporarily Christianity-Islam relationship
Keywords: Christianisme -- Oman

al-Ḥamalāt al-tanṣīrīyah ilá ʻUmān wa-al-ʻalāqah al-muʻāṣirah bayna al-Naṣrānīyah wa-al-Islām: dirasah = Evanglical [sic] missions to Oman and the contemporarily Christianity-Islam relationship - Ḥusaynī, Sulaymān ibn Sālim ibn Nāṣir (Dār al-Ḥikmah, 2006)
Keywords: Christianisme -- Oman

The Expansion of Christianity in the Pre-Islamic Middle East: from Edessa to 'Uman - Atchison-Day, Susan (University of Arizona, 2020)
Keywords: Christianisme -- Oman

Christianity in Oman: Ibadism, religious freedom, and the church - Thompson, Andrew David (Christianities of the World, 2019)
Keywords: Christianisme -- Oman